2017
DOI: 10.1016/j.ijcard.2016.10.074
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous electrical vagal nerve stimulation prior to coronary reperfusion in a canine ischemia-reperfusion model markedly reduces infarct size and prevents subsequent heart failure

Abstract: Short-term iVNS delivered prior to coronary reperfusion markedly reduced infarct size and preserved cardiac function one month after AMI. The bradycardic effect plays an important role in the beneficial effect of iVNS. How other mechanisms contribute to the reduction of infarct size remains to be studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Given the important role of HR and myocardial contractility on MVO2, this drug-device combination has great potential. In fact, a preclinical model of AMI showed that the combination of a pLVAD with either ivabradine (a drug that reduces HR) or with vagal stimulation (which also lowers HR) reduced infarct size while maintaining systemic perfusion [ 67 , 112 ]. The efficacy of drug-device combinations has not yet been tested clinically.…”
Section: Future Uses Of Acute Unloadingmentioning
confidence: 99%
“…Given the important role of HR and myocardial contractility on MVO2, this drug-device combination has great potential. In fact, a preclinical model of AMI showed that the combination of a pLVAD with either ivabradine (a drug that reduces HR) or with vagal stimulation (which also lowers HR) reduced infarct size while maintaining systemic perfusion [ 67 , 112 ]. The efficacy of drug-device combinations has not yet been tested clinically.…”
Section: Future Uses Of Acute Unloadingmentioning
confidence: 99%
“…One recently developed method for activating the vagus electrically is intravenous VNS (iVNS), which was recently found to reduce infarct size in an animal model of myocardial infarction [ 73 ]. In that study, compared to control dogs whose relative infarct size was 13.3%, dogs receiving iVNS immediately post-infarct had a 2.4% infarct size, and those receiving it 90min later had a 4.5% infarct size.…”
Section: Implications For Prevention and Treatment: Activating Thementioning
confidence: 99%
“…Vagal nerve stimulation (VNS) is a device therapy that directly and electrically activates the parasympathetic nerve. In animal experiments, VNS has shown significant therapeutic benefits for various cardiovascular diseases, including myocardial infarction (14) , fatal arrhythmia (15) , and chronic heart failure (16) . VNS has been used in patients with heart failure (17) and epilepsy (18) .…”
mentioning
confidence: 99%